Meningkatkan Hasil Belajar Siswa dengan Model Problem Based Learning (PBL) pada Materi Kesetraan Laki-Laki dan Perempuan Kelas 10 di SMA Katolik Cinta Kasih Kota Tebing Tinggi - Arvin Simaremare; Nerita Setiyaningtiyas; Christianus Aditya Kurniawan (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve student learning outcomes at SMA Katolik Cinta Kasih in Tebing Tinggi through the application of the Problem-Based Learning (PBL) model. The background of this research is based on the issue of low student success rates in conventional learning, characterized by a lack of active participation and understanding of concepts. PBL was chosen as it encourages students to be more critical, analytical, and independent in solving real-world problems. This research employed a quasi-experimental approach, involving two classes as samples. The results showed that the implementation of PBL significantly improved student learning outcomes compared to traditional teaching methods. Additionally, PBL was proven effective in increasing student motivation and engagement during the learning process. Therefore, PBL is recommended as a learning strategy to enhance student success at SMA Katolik Cinta Kasih, Tebing Tinggi in catholic Religius Education subject.